Cj1199 Affect the Development of Erythromycin Resistance in Campylobacter jejuni through Regulation of Leucine Biosynthesis - Hao, Haihong; Li, Fei; Han, Jing; Foley, Steven L.; Dai, Menghong; Wang, Xu; Wang, Yulian; Huang, Lingli; Sun, Yawei; Liu, Zhenli; Yuan, Zonghui (Frontiers in Microbiology, 2017)
The aim of this study was to reveal the biological function of Cj1199 which was overexpressed in the laboratory induced erythromycin resistant strains. The Cj1199 deletion mutant (ΦCj1199) was constructed via insertional inactivation from its parent strain C. jejuni NCTC11168. The ΦCj1199 and NCTC11168 were then subjected to microarray and real-time PCR to find gene pathway of Cj1199. The antimicrobial susceptibility, antimicrobial resistance development, growth characteristics and leucine metabolism were examined to confirm the biological function of Cj1199. Our result showed that a total of 20 genes were down-regulated in ΦCj1199. These genes were mainly involved in leucine biosynthesis, amino acid transport and periplasmic/membrane structure. Compared to NCTC11168, ΦCj1199 was difficult to acquire higher-level erythromycin resistance during the in vitro step-wise selection. The competition growth and leucine-dependent growth assays demonstrated that ΦCj1199 imposed a growth disadvantage under pressure of erythromycin and in the leucine-free medium. In conclusion, Cj1199 gene may directly regulate the leucine biosynthesis and transport and indirectly affect the development of erythromycin resistance in C. jejuni.